Storage of packed red blood cells impairs an inherent coagulation property of erythrocytes - Öhlinger, Thomas; Müllner, Ernst W.; Fritz, Magdalena; Werning, Maike; Baron-Stefaniak, Joanna; Jungbauer, Christof; Baron, David M.; Salzer, Ulrich (Frontiers in Physiology, 2022)
Storage of packed red blood cells (PRBCs) is associated with changes in erythrocytes that over time increasingly impair cellular function and potentially contribute to adverse effects associated with blood transfusion. Exposure of phosphatidylserine (PS) at the outer membrane leaflet of erythrocytes and shedding of microvesicles (MVs) during PRBC storage are alterations assumed to increase the risk of prothrombotic events in recipients. Here, we used rotational thromboelastometry to study the coagulation process in blood samples with erythrocytes from stored PRBCs reconstituted with freshly prepared platelet-rich plasma. We explored the influence of following effects on the coagulation process: (i) PRBC storage duration, (ii) differences between erythrocytes from stored PRBCs compared to freshly drawn erythrocytes, and (iii) the contribution of added MVs. Interestingly, despite of a higher fraction of PS-positive cells, erythrocytes from PRBCs stored for 6 weeks revealed longer clotting times than samples with erythrocytes stored for 2 or 4 weeks. Further, clotting times and clot formation times were considerably increased in samples reconstituted with erythrocytes from stored PRBCs as compared to fresh erythrocytes. Moreover, MVs added to reconstituted samples elicited only comparably small and ambiguous effects on coagulation. Thus, this study provides no evidence for an amplified clotting process from prolonged storage of PRBCs but on the contrary implicates a loss of function, which may be of clinical significance in massive transfusion. Our observations add to the increasing body of evidence viewing erythrocytes as active players in the clotting process.